Tax Revenues: Taxpayer Compliance as Intervening - M Firza Alpi; Hefriansyah Hefriansyah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
This study aims to analyze the effect of the number of tax audits and tax sanctions on income tax receipts through taxpayer compliance as an intervening variable at KPP Pratama Medan Timur. This study uses primary data by conducting direct research in the field as many as 44 respondents through a questionnaire with a Likert scale. The statistical method used with Path Analysis. By using the SPSS 26 program. The results of path analysis found that: the number of tax audits has an effect on tax revenues, but tax sanctions have no effect partially. the number of tax audits and tax sanctions have a significant effect on taxpayer compliance. However, partially, only tax audits have a positive and significant effect. tax audits, Tax sanctions and taxpayer compliance have a positive and significant effect on tax revenues at KPP Pratama Medan Timur, but partially only taxpayer compliance has a positive and significant effect. Taxpayer compliance is able to mediate the influence of tax audits on taxpayers. However, it cannot mediate/intervening tax sanctions against tax revenues at KPP Pratama Medan Timur.